2022
DOI: 10.7860/jcdr/2022/53064.16018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Phenotypic Methods Including E-Test, Cefoxitin and Oxacillin Disk Diffusion for Detection of Methicillin Resistant Staphylococcus aureus

Abstract: Introduction: Methicillin-Resistant Staphylococcus aureus (MRSA) has spread throughout the world as a hospital and communityacquired illness. Although a variety of strategies have been employed, laboratory identification of MRSA remains a difficulty. Aim: To examine several phenotypic approaches for accuracy results, with an (Epsilometer) E-test based method serving as the gold standard for MRSA identification. Materials and Methods: A prospective observational study was conducted in the Microbiology departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Overall, when the results of the disc diffusion test and the E-test were compared with the genotypically confirmed methicillin-resistant staphylococci, our results found the E-test to be more in accordance with the presence of mecA or mecC genes in staphylococci as compared to the disc diffusion test. Our results are similar to the findings of Wu et al and Gupta et al that demonstrated that the E-test is the gold standard method for detecting methicillin resistance [ 69 , 70 ] rather than disc diffusion testing. Our finding also supports the use of both oxacillin and cefoxitin in disc diffusion testing to prevent false negatives and that cefoxitin alone is not reliable in predicting the presence of the mecA/mecC gene, also reported by Wu et al [ 69 ].…”
Section: Discussionsupporting
confidence: 92%
“…Overall, when the results of the disc diffusion test and the E-test were compared with the genotypically confirmed methicillin-resistant staphylococci, our results found the E-test to be more in accordance with the presence of mecA or mecC genes in staphylococci as compared to the disc diffusion test. Our results are similar to the findings of Wu et al and Gupta et al that demonstrated that the E-test is the gold standard method for detecting methicillin resistance [ 69 , 70 ] rather than disc diffusion testing. Our finding also supports the use of both oxacillin and cefoxitin in disc diffusion testing to prevent false negatives and that cefoxitin alone is not reliable in predicting the presence of the mecA/mecC gene, also reported by Wu et al [ 69 ].…”
Section: Discussionsupporting
confidence: 92%